2014
DOI: 10.1038/cgt.2014.29
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of miR-221/222 enhances sensitivity of breast cancer cells to tamoxifen through upregulation of TIMP3

Abstract: Aberrantly expressed microRNAs (miRNAs) are involved in breast tumorigenesis. It is still unclear if and how miRNAs-221/222 are implicated in breast cancer and the resistance to estrogen receptor modulator tamoxifen. We investigated the roles and mechanisms of miR-221/222 in breast cancer cells, particularly in modulating response to tamoxifen therapy. MCF-7 and MDA-MB-231 breast cancer cells were transfected with antisense oligonucleotides AS-miR-221 and AS-miR-222 and their expression of miR-221 and miR-222 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 50 publications
2
66
0
2
Order By: Relevance
“…The function of the transferred anti-miRNA was assessed in drug sensitivity analyses (29,33). Primed MSCs were transfected with Cy5-anti-miR-222 or Cy5-control anti-miR.…”
Section: Reverse Dormancy By Targeted Mir-222/223mentioning
confidence: 99%
“…The function of the transferred anti-miRNA was assessed in drug sensitivity analyses (29,33). Primed MSCs were transfected with Cy5-anti-miR-222 or Cy5-control anti-miR.…”
Section: Reverse Dormancy By Targeted Mir-222/223mentioning
confidence: 99%
“…42 However, the miR-221/222 cluster is associated with tamoxifen resistance in breast cancer cells. 43,44 Miller et al 45 reported that miR-221/222 expressions were upregulated in endocrine therapy-resistant luminaltype breast cancer cells. MiR-221/222 are negative regulators of p27 kip1 , a cell cycle inhibitor and tumor suppressor, [46][47][48][49][50] and upregulated expressions of these miRNAs and significant reductions in p27 kip1 levels have been reported in tamoxifen-resistant breast cancer cells; therefore, miR-221/222 might regulate tamoxifen sensitivity via the direct targeting of p27 kip1 .…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…76 Transfection of ASOs AS-miR-221 and AS-miR-222 into breast cancer cells dramatically inhibited the expression of miR-221 and miR-222, respectively, and the suppression of miRNA-221/222 increased the sensitivity of ER-positive MCF-7 breast cancer cells to tamoxifen. 77 A recent study reported a tumor treatment strategy that simultaneously disturbs the function of multiple oncogenic miRNAs. The strategy uses a viral vector to mediate the expression of an artificially designed interfering long non-coding RNA (lncRNA).…”
Section: Potential Value Of Emt-related Mirnas In the Treatment Of Brmentioning
confidence: 99%